2015
DOI: 10.1016/j.jare.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the bactericidal activity of selected essential oils to Aeromonas spp.

Abstract: Diseases of fishes caused by Aeromonas spp. are common, have broad host ranges and may cause high mortality. Treatments of captive-reared populations using antimicrobials are limited with concerns for bacterial resistance development and environmental dissemination. This study was done to determine whether selected plant-derived essential oils were bactericidal to Aeromonas spp. Initially, twelve essential oils were evaluated using a disk diffusion assay to an isolate of A. salmonicida subsp. salmonicida, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
2
30
1
2
Order By: Relevance
“…Besides, 53.6 % pseudomonads, 53.1 % streptococci and 50 % of Budvicia aquatica and Leminorella ghirmontii strains were also sensitive to LMO. In general, the antimicrobial properties of LMO and its practical application potential are comparable to oregano oil and only surpassed by thyme oil (Starliper et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, 53.6 % pseudomonads, 53.1 % streptococci and 50 % of Budvicia aquatica and Leminorella ghirmontii strains were also sensitive to LMO. In general, the antimicrobial properties of LMO and its practical application potential are comparable to oregano oil and only surpassed by thyme oil (Starliper et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among them thyme oil, oregano oil and, lately, lemongrass oil have been evaluated for their antioxidant and antimicrobial properties (Tongnuanchan and Benjakul 2014). There are several reports where different bacteria have been tested for their sensitivity to LMO components (Taweechaisupapong et al 2012;Starliper et al 2015;Olorunnisola et al 2014). In one of the most extensive studies, Singh et al (2011) tested the antimicrobial activity of LMO against 1114 strains belonging to 29 genera and 105 species of microbes (molds, yeasts and bacteria) isolated from clinical cases, environment (water, air, soil, droppings of lizards and birds), food and healthy animals.…”
Section: Introductionmentioning
confidence: 99%
“…Setiawati et al (2016) observed that the addition of cinnamon leaf extract and powder significantly increased the fish specific growth rate, feed efficiency, protein retention as compared to the control. Among its proven biological activities, several reports highlighted its antimicrobial activity (Singh et al 2007 andStarliper et al 2015), primarily attributable to cinnamaldehyde present in the bark of the plant (Wong et al 2014 The overall objective of the proposed study was to investigate the effect of cinnamon on growth performances and to control bacterial load of H. fossilis. The specific objectives were: preparation of commercial feed with different percentage of cinnamon, culture of experimental fish, determination of growth performance parameters such as ADG, SGR, FCR, condition factor and survival rate and determination of bacterial load in experimental fish species.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our results, a previous study reported MBC values of around 0.31% (v/v) in fish-borne Aeromonas spp. (Starliper et al 2015). In contrast, lemongrass oil exerted only a minor effect on C. freundii and P. mirabilis and a lower number of isolates were found to be susceptible (Singh et al 2011).…”
Section: Discussionmentioning
confidence: 99%